Exploration on Drivers’ Perception Towards Roadway Inventory Elements - Azlina, Ismail; Intan Suhana, Mohd Razelan; Mandiartha, Putu; Nadia, Arib (Springer, Singapore, 2018)
Accidents due to driver’s fault occur in many ways including human perception and driving behaviour. It varies with age, emotion, belief and attitude. In addition, the fact that accident can happen due to poor roadway inventory management should not be neglected. Therefore, this study is intended to explore how drivers’ perception subjectively reviews the roadway inventory elements performance that might be a potential factor affecting road safety. To achieve this, Jalan Kuantan-Gambang was chosen as a study location. This study was conducted using a qualitative study by means of questionnaires distribution. Then the average index method was performed to indicate the driver’s perception towards the roadway inventory elements performance. The results explain that drivers’ perception of different age affects the performance of roadway elements, where attention for older drivers during road design and construction are essential.